2022
DOI: 10.3389/fpubh.2021.796663
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Triglyceride–Glucose Index and the Risk of Type 2 Diabetes Mellitus in an Older Chinese Population Aged Over 75 Years

Abstract: BackgroundThe association between the triglyceride–glucose (TyG) index and type 2 diabetes mellitus (T2DM) in older adults has not been fully understood. This research aims to explore the association between the TyG index and the incidence of T2DM in an older Chinese population aged over 75 years.MethodsThis longitudinal analysis study was performed based on a database from a health check screening program in China. The participants were stratified based on the quintile ranges of the TyG index (Q1 to Q5 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The optimal thresholds for predicting the risk of T2D in males and females were 8.76 and 8.64, respectively, consistent with this study. Similarly, Fu et al showed that TyG could better predict T2D risk compared to TG/HDL in the older Chinese population [ 23 ], thereby supporting this study.…”
Section: Discussionsupporting
confidence: 86%
“…The optimal thresholds for predicting the risk of T2D in males and females were 8.76 and 8.64, respectively, consistent with this study. Similarly, Fu et al showed that TyG could better predict T2D risk compared to TG/HDL in the older Chinese population [ 23 ], thereby supporting this study.…”
Section: Discussionsupporting
confidence: 86%
“…The triglyceride-glucose (TyG) index, conveniently calculated by triglyceride and fasting glucose levels, has been regarded as a good alternative surrogate marker for the established parameters of IR [ 7 ]. Accumulating evidence indicated that the TyG index is associated with cardiovascular and metabolic risk, predominantly cardiovascular disease [ 8 11 ], type 2 diabetes mellitus [ 12 ], stroke [ 13 , 14 ], arterial stiffness [ 11 , 15 , 16 ], vascular damage [ 17 , 18 ] and even death [ 19 ]. Recently, a few studies reported that a higher TyG index was also associated with an increased risk of sarcopenia or low muscle mass in older populations [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The related diseases brought by obesity and the in uence of obesity on subjective health may be the mechanism of the obesity-HRQoL association. The long-term impact of obesity on health is multi-sided, and it is involved in the pathogenesis of chronic diseases such as diabetes, hypertension, and dyslipidemia, which coordinate with various diseases and indirectly affect health status and HRQoL [44].…”
Section: Discussionmentioning
confidence: 99%